Inhibition of Vascular Growth by Modulation of the Anandamide/Fatty Acid Amide Hydrolase Axis. Issue 12 (7th October 2021) - Rieck, Sarah; Kilgus, Sofia; Meyer, Johanna H.; Huang, Hao; Zhao, Lan; Matthey, Michaela; Wang, Xin; Schmitz-Valckenberg, Steffen; Fleischmann, Bernd K.; Wenzel, Daniela
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Pathological angiogenesis is a hallmark of various diseases characterized by local hypoxia and inflammation. These disorders can be treated with inhibitors of angiogenesis, but current compounds display a variety of side effects and lose efficacy over time. This makes the identification of novel signaling pathways and pharmacological targets involved in angiogenesis a top priority. Approach and Results: Here, we show that inactivation of FAAH (fatty acid amide hydrolase), the enzyme responsible for degradation of the endocannabinoid anandamide, strongly impairs angiogenesis in vitro and in vivo. Both, the pharmacological FAAH inhibitor URB597 and anandamide induce downregulation of gene sets for cell cycle progression and DNA replication in endothelial cells. This is underscored by cell biological experiments, in which both compounds inhibit proliferation and migration and evoke cell cycle exit of endothelial cells. This prominent antiangiogenic effect is also of pathophysiological relevance in vivo, as laser-induced choroidal neovascularization in the eye of FAAH −/− mice is strongly reduced. Conclusions: Thus, elevation of endogenous anandamide levels by FAAH inhibition represents a novel antiangiogenic mechanism.